KEPEMIMPINAN SPIRITUALITAS FRANSISKAN - Victoria Korina Cristina; Usman Radiana; M. Syukri (Universitas Tanjungpura, 2021)
AbstractThe research objective was to comprehensive information about the leadership ofFranciscan spirituality at the Pontianak Good Shepherd Education Foundation. Theresearch method used is descriptive qualitative by using a type of case study research.The Head of the Foundation as the research subject, the Foundation Management, thePrincipal of the School, and the Teacher as the informant. Data collection techniquesare by interview, observation, and documentation. The conclusion of the research isthat the chairman of the foundation has a firm character, serves with a spirit ofbrotherhood, is communicative and a good listener, is participatory-democratic, andthe chairman of the foundation is more likely to adopt a servant leadership style. Livingthe values of togetherness and brotherhood, ecology, faith and morals. The values oftogetherness and brotherhood, ecology, faith and morals have been implementedproperly. As well as striving to develop leadership in Franciscan spirituality bydeveloping existing programs, maintaining good relationships with subordinates, andcompiling special materials that contain typical Franciscan-Capuchin values. Theimplication of these findings can help introduce the work of the Capuchin Order ofPontianak Province, especially in the field of education and can increase knowledgeabout the values of franciscan spirituality.Keywords:Franciscan Spirituality, Leadership, The Foundation’s Chairman